2001
DOI: 10.1063/1.1406500
|View full text |Cite
|
Sign up to set email alerts
|

La@C 60 : A metallic endohedral fullerene

Abstract: We have produced an endohedrally doped fullerene that shows a metal-like density of states at the Fermi level. Individual La@C 60 clusters deposited onto graphite exhibit a zero band gap as observed by scanning tunneling spectroscopy on single clusters at room temperature. Moreover, we find that an isolated La@C 60 cluster on graphite shows a reversible opening of a band gap at a transition temperature of ϳ28 K. The transition is associated with a freezing of the vibrational motion of the La atom inside the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…latter in a low coverage region. 18 The STM data have been measured at room temperature using a chemically etched tungsten tip. 36 The tip was prepared for scanning tunneling spectroscopy measurements as described previously.…”
Section: A Production Of Carbon Clustersmentioning
confidence: 99%
“…latter in a low coverage region. 18 The STM data have been measured at room temperature using a chemically etched tungsten tip. 36 The tip was prepared for scanning tunneling spectroscopy measurements as described previously.…”
Section: A Production Of Carbon Clustersmentioning
confidence: 99%
“…This image is similar to a bright spherical feature for La@C 60 on a HOPG reported previously. 4 It was reported that neither La@C 60 nor Ce@C 60 molecules formed an island on the HOPG at room temperature. 4 The Dy@C 60 molecules are also adsorbed on the surface without islands and do not migrate at 295 K. No spots ascribable to the Dy atoms are observed around the nearly spherical image.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the adsorption characteristics of metallofullerenes on semiconductor surfaces have been studied extensively by STM. [2][3][4][5][6] A STM image of Sc 2 @C 84 adsorbed on Si(100)-(2ϫ1) surface was first reported by Shinohara et al and showed a nearly spherical structure of the Sc 2 @C 84 molecule. 2 The first layer of Sc 2 @C 84 was not ordered, owing to strong interactions between the surface and the molecules.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…
Endohedral metallofullerenes (fullerenes with metal atom(s) encapsulated), as a novel form of carbon-related materials, [1] have attracted special attention for their potential applications [2][3][4][5][6][7][8][9][10] in electronic devices, [2,3] biomedical fields such as therapeutic medicine, [4,5] and a new generation of magnetic resonance imaging (MRI) contrast agents, [6][7][8] etc.Recently, the polyhydroxylated Gd@C 82 material was found to possess a very high efficiency of inhibiting cancer growth in vivo, and to have a strong capacity to improve immunity and interfere with tumor invasion in normal muscle cells. Unlike conventional anticancer chemicals that use a high toxicity to kill cells, this material shows non-toxicity in vivo and in vitro and does not kill normal cells directly.
…”
mentioning
confidence: 99%